Immigration to the Land of Redistribution - Tito Boeri (London School of Economics and Political Science (LSE), European Institute, 2010)
Negative perceptions about migrants in Europe, the Continent with the largest social policy rogrammes, are driven by concerns that foreigners are a net fiscal burden. Increasing concerns are pressing Governments, in the midst of the recession, to reduce welfare access by migrants or further tighten migration policies. Are there politically feasible alternatives to these two hardly enforceable (and procyclical) policy options? In this paper we look at economic and cultural determinants of negative perceptions about migrants in Europe. Based on a simple model of the perceived fiscal effects of migration and on a largely unexploited database (EU-Silc), we find no evidence that legal migrants, notably skilled migrants, are net recipients of transfers from the state. However, there is evidence of "residual dependency" on contributory transfers and self-selection migrants more likely to draw on welfare in the countries with the most generous welfare state. Moreover, those favouring redistribution to the poor do not overlap with those considering migrants as part of the same community. A way out of the migration dilemma facing Europe involves i. co-ordinating safety nets across the EU, and ii. adopting explicitly selective migration policies. Other options involve restricting welfare access by migrants and subsidising voluntary return migration of lowskilled migrants during the recession.
Keywords: J38; J5; 330; Migration policy; Welfare access; Fiscal externality